The meV XUV‐RIXS facility at UE112‐PGM1 of BESSY II. (26th April 2022) - Bauer, Karl; Schmidt, Jan-Simon; Eggenstein, Frank; Decker, Régis; Ruotsalainen, Kari; Pietzsch, Annette; Blume, Thomas; Liu, Chun-Yu; Weniger, Christian; Siewert, Frank; Buchheim, Jana; Gwalt, Grzegorz; et al.
Abstract : Resonant inelastic X‐ray scattering in the XUV‐regime with few meV bandwidth has been implemented at the dedicated low‐energy beamline UE112‐PGM1 at BESSY II. Abstract : Resonant inelastic X‐ray scattering in the XUV‐regime has been implemented at BESSY II, pushing for a few‐meV bandwidth in inelastic X‐ray scattering at transition metal M ‐edges, rare earth N ‐edges and the K ‐edges of light elements up to carbon with full polarization control. The new dedicated low‐energy beamline UE112‐PGM1 has been designed to provide 1 µm vertical and 20 µm horizontal beam dimensions that serve together with sub‐micrometre solid‐state sample positioning as the source point for a high‐resolution plane grating spectrometer and a high‐transmission Rowland spectrometer for rapid overview spectra. The design and commissioning results of the beamline and high‐resolution spectrometer are presented. Helium autoionization spectra demonstrate a resolving power of the beamline better than 10 000 at 64 eV with a 300 lines mm −1 grating while the measured resolving power of the spectrometer in the relevant energy range is 3000 to 6000.